New York in Slices: The Victorian Origins of The Bonfire of the Vanities. (23rd February 2022) - Abraham, Adam
Abstract: The Bonfire of the Vanities, Tom Wolfe's first novel, was a bestseller in the 1980s, when it captured its historical moment of yuppie excess, urban corruption, and vanity. Less recognized today are the book's origins as an experiment in reviving Victorian modes of publication. Taking Dickens and Thackeray, Balzac and Zola as his models, Wolfe planned to write what he conceived of as a new nineteenth-century novel—multiplot and multivalent—an anatomy of New York City. What is more, The Bonfire of the Vanities was first published serially, in Rolling Stone magazine, from 1984 to 1985. This article will explore the Victorian provenance of Wolfe's novel, in particular by rereading the original serial parts.